Eight-and-a-half syndrome in pontine cavernoma: a rare presentation - Nair, Shruti M.; Kasturi, Nirupama; P., Jayasri; Stephen, Mary (International Journal of Advances in Medicine, 2023)
Cavernous vascular anomalies are varied in form, and cavernomas are very rare lesions commonly found in the supra-tentorial region. Eight-and-a-half syndrome includes horizontal gaze palsy, internuclear ophthalmoplegia, and facial nerve palsy, which is rare in clinical practice. Etiologies are commonly infarct and demyelination. Cavernomas are space-occupying lesions that can lead to life-threatening complications due to haemorrhage, and cavernomas resulting in "eight-and-a-half syndrome" are extremely rare. We report a case of pontine cavernoma presenting as "eight and half syndrome," which worsened systemically, but with timely intervention, the patient recovered completely with good follow-up and an intact permanent tarsorrhaphy.